2019
DOI: 10.1186/s13046-019-1078-2
|View full text |Cite
|
Sign up to set email alerts
|

MiR-9 promotes tumorigenesis and angiogenesis and is activated by MYC and OCT4 in human glioma

Abstract: Background Glioma, characterized by its undesirable prognosis and poor survival rate, is a serious threat to human health and lives. MicroRNA-9 (miR-9) is implicated in the regulation of multiple tumors, while the mechanisms underlying its aberrant expression and functional alterations in human glioma are still controversial. Methods Expressions of miR-9 were measured in GEO database, patient specimens and glioma cell lines. Gain- and loss-of-function assays were applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 48 publications
4
91
2
Order By: Relevance
“…The set includes miR-148a and miR-9-5p, both previously associated with glioma angiogenesis (Kim et al, 2014;Zhang et al, 2019a;Madelaine et al, 2017;Yi and Gao, 2019) and poor survival. Our results are concordant with previous studies (Chen et al, 2019) reporting that when miR-9 is delivered to human umbilical ECs (HUVEC) via GBM-derived EVs, its expression levels in HUVECs directly correlated with the resulting tubule formation count and length. Our results are also concordant with previous studies (Wong et al, 2015) reporting that the silencing of miR-148a normalizes the aberrant tumor vasculature in mouse models of GBM.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The set includes miR-148a and miR-9-5p, both previously associated with glioma angiogenesis (Kim et al, 2014;Zhang et al, 2019a;Madelaine et al, 2017;Yi and Gao, 2019) and poor survival. Our results are concordant with previous studies (Chen et al, 2019) reporting that when miR-9 is delivered to human umbilical ECs (HUVEC) via GBM-derived EVs, its expression levels in HUVECs directly correlated with the resulting tubule formation count and length. Our results are also concordant with previous studies (Wong et al, 2015) reporting that the silencing of miR-148a normalizes the aberrant tumor vasculature in mouse models of GBM.…”
Section: Discussionsupporting
confidence: 92%
“…To further elucidate non-conventional angiogenic pathways in GBM, we here examine the GSC-EV-mediated transfer of extracellular RNAs (exRNAs) from human GSCs to human brain microvascular ECs (HBMVECs) in vitro by molecular profiling and to ECs in vivo via histoepigenetic analysis by computational deconvolution. EV-derived miRNAs are known to convey growthpromoting and angiogenic signaling in GBM (Beyer et al, 2017;Chen et al, 2019;Todorova et al, 2017;Wong et al, 2015); however, the molecular events controlling this process in HBMVECs are largely unknown. We hypothesized that GSC-derived ex-RNAs, along with more conventional vascular GFs, jointly modulate the gene-expression landscape of ECs to promote angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, cancer cells could escape immune attack by downregulating NKG2D ligands including MICA, MICB, and UL16-binding protein. TAP transporter associated with antigen processing, MHC-I major histocompatibility complex class I, MICA/B MHC-I chain-related molecules A/B, IDO indoleamine 2, 3-dioxygenase, ULBP UL16-binding protein cancer (NSCLC), and glioma might contribute to enhanced immune tolerance in the tumor microenvironment [57][58][59]. Meanwhile, some endoplasmic reticulum stress-associated miRNAs such as miR-346 regulates immune response by directly targeting TAP1 or indirectly suppressing the expression of MHC-I molecules and interferon (IFN) signaling pathway [60].…”
Section: The Role Of Mirnas In Cancer Immune Evasionmentioning
confidence: 99%
“…found that lung cancer‐derived suppressing miR‐23a in exosomes could upregulate prolyl hydroxylase 1 and 2 (PHD1 and 2), accumulated hypoxia‐inducible factor‐1 alpha (HIF‐1 alpha) in endothelial cells so as to induce angiogenesis and promote vascular permeability (Table ). In human glioma, Chen et al . measured the expression of miR‐9 and elucidated that upregulated exosomal miR‐9 released from glioma cells was absorbed by vascular endothelial cells and targeted COL18A1, THBS2, PTCH1 and PHD3, contributing to promoted angiogenesis (Table ).…”
Section: Exosome and Tumor Developmentmentioning
confidence: 99%
“…Under the hypoxic circumstance, Hsu et al 50 found that lung cancer-derived suppressing miR-23a in exosomes could upregulate prolyl hydroxylase 1 and 2 (PHD1 and 2), accumulated hypoxia-inducible factor-1 alpha (HIF-1 alpha) in endothelial cells so as to induce angiogenesis and promote vascular permeability ( Table 1). In human glioma, Chen et al 51 measured the expression of miR-9 and elucidated that upregulated exosomal miR-9 released from glioma cells was absorbed by vascular endothelial cells and targeted COL18A1, THBS2, PTCH1 and PHD3, contributing to promoted angiogenesis (Table 1). Similarly, glioma stem cells (GSC)-derived activated exosomal miR-26a downregulated PTEN and promoted angiogenesis of human brain microvascular endothelial cell (HBMEC) via PI3K/Akt signaling pathway 52 (Table 1).…”
Section: Cancer Metastasismentioning
confidence: 99%